Cognitive Assessment in SARS-CoV-2 Patients: A Systematic Review - Biagianti, Bruno; Di Liberto, Asia; Nicolò Edoardo, Aiello; Lisi, Ilaria; Nobilia, Letizia; de Ferrabonc, Giulia Delor; Zanier, Elisa R.; Stocchetti, Nino; Brambilla, Paolo (Frontiers in Aging Neuroscience, 2022)
Background. Post-infective SARS-CoV-2 patients might show both short- and long-term cognitive deficits within the dysexecutive/inattentive spectrum. However, little is known about which cognitive alterations are commonly found in COVID-19 survivors and which psychometric tools practitioners should adopt when assessing cognition in this population. The present work aimed at providing an overview of neuropsychological deficits commonly observed and tests most suited for detecting cognitive sequelae of SARS-CoV-2 infection. Methods. This review followed PRISMA guidelines and was pre-registered on PROSPERO (CRD42021253079). Observational studies quantitatively assessing cognition in post-infective SARS-CoV-2 patients were considered. From 711 retrieved articles, 21 studies were included. Presence of comorbidities and disease severity were controlled for. Results. The majority of studies (N=15) adopted I-level tools. The most frequently administered screeners were the Montreal Cognitive Assessment (MoCA) and the Mini-Mental State Examination (MMSE) - with the former being able to detect mild and the latter moderate/severe deficits. Among II-level tests, those assessing attention and executive functions (EFs) were highly represented. Remotely-delivered tests yielded lower percentages of cognitive impairment. Overall, cognitive domains often found to be impaired were EFs, attention and memory. Conclusions. Cognitive sequelae in post-infective SARS-CoV-2 patients can be detected with neuropsychological testing. Depending on the psychometric features the likelihood of observing cognitive deficits can vary. Further studies are needed on larger sample sizes and focusing on the clinical usefulness of II-level tools. Early detection and intervention for emerging cognitive deficits should be the preventive aim of health services.